If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 + -5n + n = n + -2 Combine like terms: -5n + n = -4n -12 + -4n = n + -2 Reorder the terms: -12 + -4n = -2 + n Solving -12 + -4n = -2 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -12 + -4n + -1n = -2 + n + -1n Combine like terms: -4n + -1n = -5n -12 + -5n = -2 + n + -1n Combine like terms: n + -1n = 0 -12 + -5n = -2 + 0 -12 + -5n = -2 Add '12' to each side of the equation. -12 + 12 + -5n = -2 + 12 Combine like terms: -12 + 12 = 0 0 + -5n = -2 + 12 -5n = -2 + 12 Combine like terms: -2 + 12 = 10 -5n = 10 Divide each side by '-5'. n = -2 Simplifying n = -2
| 14-n-7=5n+1 | | 1-7k=1+3k+4k | | 8-9x+10x=5 | | 8b+6=-9+3b | | 32-6b-5b=7.25 | | 3+3x=x-3 | | 1+7r=-7+3r | | 2(5x-1)=3x(x+1) | | 8x-2=-7+7x | | 2x+8=-5 | | -107=3-10x | | 7n+3=-67 | | 7=6-v | | 5c-3-4c=2c+2 | | 160+(16x+32)=180 | | 3a=1 | | (3x-4)(x^2-5x+1)= | | -9x^2+5x+12=0 | | 6(2a^2+3a)=18-12a | | 4x-18+4x=180 | | 15-(2m+4)=4+2m-13 | | -3y(6y+7)= | | 6x-20=4x+40 | | 7.34*1.8= | | 3+6x=-4y | | 7x^2-4x+.5717285714=0 | | -8r-4=7r-4 | | 8x^2+9x+6.5=0 | | x^2+3.81x+3.61=0 | | 2.5d=40+50 | | .2(d-6)=.3d+5-3+.1d | | x^2+2.40x+1.44=0 |